The Newly Discovered Old Printed Charms of Vardadzor Village of Gegharkunik Province - Grigoryan, Satenik (Bulletin of Yerevan University B: Philology, 2024)
The newly discovered (recently discovered) first-printed Amulet in the form of a scroll belongs to the Margaryan family, who settled in the village of Vardadzor, Msho province from Western Armenia. Despite some changes and damage, it was possible to find out that this unit belongs to a series of amulet-scrolls published in 1698, in the printing house of Grigor Marzvanets, in Constantinople. It is distinguished by rich iconography and diversity of prayers. The scroll amulet with the exact date (1698) almost completely copies the cultural features of the first printing and its characteristic artistic design, published in Constantinople in the 17th century. It belongs to the series of scroll-shaped amulets (in addition to scroll-shaped amulets, there are also book-shaped amulets, which are a unique example). Unfortunately, the Amulet is completely damaged and divided into small parts. Due to damage, the content has been changed. Compared to other units, the prayers and the engraving managed to restore the existing shortcomings. Despite its fragmentation, the amulet in the form of a scroll contains about eighteen prayers. The content begins with the famous work of Nerses Shnorali “I confess my faith” and ends with the prayer “Prayer to bind demons.” Under the influence of handwritten Conspiracies, the printed Conspiracy also inherited the artistic composition typical of miniatures. Miniature painting was replaced by iconography, but the thematic character remained unchanged. The presence of images indicates an important belief that in this way the amulets acquire greater power and the ability to influence is enhanced. Illustrations for incantations generally precede subsequent prayers. The number of available engravings on the archetype reaches 13.